PENGARUH PENGGUNAAN MEDIA POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Alviona, Chindy; Ulwan Syafrudin; Miranda Abung; Frida Destini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was the low learning outcomes of fourth-grade studentsat SD Negeri 1 Mataram. This research aims to investigate the impact ofinteractive PowerPoint media on students' learning outcomes. The researchmethod employs a quasi-experimental design with a non-equivalent control groupdesign. The sample consists of 30 students from class IVA as the control groupand 29 students from class IVB as the experimental group; the sample emergesfrom non-probability sampling via saturated sampling technique. Data collectiontechniques include tests and non-tests. Data analysis employs simple linearregression testing, revealing a 77% effect size for the variable. The results show apositive and significant influence from the application of interactive PowerPointmedia on the mathematics learning outcomes of fourth-grade students in class IVBat SD Negeri 1 Mataram for the 2025/2026 academic year.